2021
DOI: 10.33714/masteb.776902
|View full text |Cite
|
Sign up to set email alerts
|

Cu, Cd, As and Hg resistance levels in Escherichia coli isolated from Mediterranean mussel and sea snail in the Southeastern Black Sea

Abstract: Marine environment is exposed to various pollutants such as heavy metals, pesticides, and antibiotics. Bacterial resistance to these pollutants is a global problem all over the world. In this study, Mediterranean mussel (Mytilus galloprovincialis) and sea snail (Rapana venosa) were collected from 12 sampling points from Artvin, Rize, Trabzon, and Giresun Coasts of Black Sea, Turkey. A total of 54 Escherichia coli isolated from Mediterranean mussel and sea snail were tested for their ability to tolerate Cu, Cd,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 23 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Moller et al (2014) reported merA in strains with phenotypic mercury resistance. In another study, mercury-resistant (7.4%) E. coli strains were isolated from mussels and sea snails, and the presence of merA was reported (Terzi and Civelek, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Moller et al (2014) reported merA in strains with phenotypic mercury resistance. In another study, mercury-resistant (7.4%) E. coli strains were isolated from mussels and sea snails, and the presence of merA was reported (Terzi and Civelek, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The ability of Hg to inhibit the growth of these bacteria isolates could be due to its high level of toxicity [48,49]. Contrastingly, most of the bacteria isolated were resistant to high concentration of Cd and Co, in tandem with this is the result of the study of Terzi and Civelek in which they observed that high concentration of Cd was still being tolerated by their bacteria isolates [17]. HMRGs namely merA (mercury), pcoC (copper), pbrT (lead), cadD (cadmium), and cnrA (cobalt and nickel) were genotyped in isolates 2, 6, 7, and 9.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, these resistance mechanisms are often conferred by natural selection or exposure to substrates containing heavy metal ions [16]. Salmonella, Escherichia coli, and Rhodobacter sphaeroides are among the bacteria that have been reported to possess multiple heavy metal resistance genes (HMRGs); hence, they are regarded as suitable for environmental remediation [6,17].…”
Section: Introductionmentioning
confidence: 99%
“…The sea snail "Rapa whelk" is a good bioindicator for metals, and its bioaccumulation is highly dependent on the level of metal pollution in the ecosystem (Liang et al 2004;Terzi & Civelek 2021), possibly because of their low motion on the sea floor (Hwang et al 2017). Despite being a seafood with notable health benefits, when Rapa whelk is consumed at high intake levels it can be seriously detrimental to health (Stancheva et al 2012).…”
Section: Introductionmentioning
confidence: 99%